Progress and Achievements in Glycosylation of Flavonoids - Khodzhaieva, Ruslana S.; Gladkov, Eugene S.; Kyrychenko, Alexander; Roshal, Alexander D. (Frontiers in Chemistry, 2021)
In recent years, the chemistry of flavonoid glycosylation has undergone significant developments. This mini-review is devoted to summarizing existing strategies and methods for glycosylation of natural and synthetic flavonoids. Herein we overviewed the reaction conditions of flavonoid glycosylation depending on the position of hydroxyl groups in a parent molecule, the degree of it conjugation with the π-system, the presence of steric factors, the formation of intramolecular hydrogen bonds, etc. Especial attention was given to the choice of the glycosyl donor moiety, which has a significant effect on the yield of the final glycosidated products. Finally, a general strategy for regioselective glycosylation of flavonoids containing several hydroxyl groups is outlined.